Dentispicotermes trapezia (Isoptera: Termitidae: Amitermitinae), a new termite species from the Pantanal-Chaco Region of South America - Scheffrahn, Rudolf H. (Zootaxa, 2024)
Dentispicotermes trapezia sp. nov. is described from the soldier and worker castes of specimens collected in Pantanal-Chaco Region of Bolivia and Paraguay. The soldiers differ from its five congeners in having a trapezoidal frontal protuberance with in-line marginal teeth. A key to Dentispicotermes soldiers is provided.